The Kurdish model of political community a vision of national liberation defiant of the nation-state - Baris, Hanifi, 1978- (Kurdish societies, politics, and international relations., 2021)
"National sovereignty entails exclusive ownership of territories and natural resources, which often leads to uncompromising domination and subjugation of life by a central political authority. In a stark contrast, the Kurdish vision of political community invokes communal sovereignty, which is detached from the nation and the territorial state"--